Relative performance of hybrid nestlings in Ficedula flycatchers: a translocation experiment - Vallin, Niclas (Blackwell Publishing Ltd, 2013)
Ecological speciation predicts that hybrids should experience relatively low fitness in the local environments of their parental species. In this study, we performed a translocation experiment of nestling hybrids between collared and pied flycatchers into the nests of conspecific pairs of their parental species. Our aim was to compare the performance of hybrids with purebred nestlings. Nestling collared flycatchers are known to beg and grow faster than nestling pied flycatchers under favorable conditions, but to experience higher mortality than nestling pied flycatchers under food limitation. The experiment was performed relatively late in the breeding season when food is limited. If hybrid nestlings have an intermediate growth potential and begging intensity, we expected them to beg and grow faster, but also to experience lower survival than pied flycatchers. In comparison with nestling collared flycatchers, we expected them to beg and grow slower, but to survive better. We found that nestling collared flycatchers indeed begged significantly faster and experienced higher mortality than nestling hybrids. Moreover, nestling hybrids had higher weight and tended to beg faster than nestling pied flycatchers, but we did not detect a difference in survival between the latter two groups of nestlings. We conclude that hybrid Ficedula nestlings appear to have a better intrinsic adaptation to food limitation late in the breeding season compared with nestling collared flycatchers. We discuss possible implications for gene flow between the two species.